Long-chain fatty acid compositions and volatile metabolite patterns of yeasts associated with wine - Tredoux, Hendrik Gabriël (University of the Free State, 1987)
A) In Chapter 1 the need for a yeast identification system in the wine industry is highlighted. The definition, as well as taxonomic development of the ascomycetous yeasts are discussed as well as the problems encountered. B) In Chapter 2 the cellular long-chain fatty acid compositions of 103 yeast strains representing 38 species related to the wine industry were determined gaschromatographically. It was possible to differentiate between most species examined as well as between some strains within species. A correlation was observed between long-chain fatty acid composition and complexity of cell differentiation, genetic recombination, carbon source- and ethylamine utilization and resistance to cycloheximide. A phylogenetic scheme for the genus Kluyveromyces was constructed on the basis of the abovementioned features. C) Chapter 3 includes the use of volatile metabolites in the identification of winery-associated yeasts. According to the results it was possible to differentiate between the Saceh. cerevisiae and S. pombe strains. D) A Discussion and Conclusions is presented in Chapter 4. This includes a discussion on the identification of wine yeasts and the relation between long-chain fatty acid composition, pseudomycelium formation, genetic recombination, carbon source- and ethylamine utilization and resistance to cycloheximide. A possible relation between the similarity in long-chain fatty acid compositions and DNA homology between yeasts strains is indicated. The use of volatile metabolites in the identification of wine yeasts is also discussed.
Dissertation (M.Sc. (Microbiology))--University of the Free State, 1987
Keywords: Saccharomyces; Fatty acids; Yeast; Viticulture